1993
DOI: 10.1099/00221287-139-11-2793
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of glucose-6-phosphate dehydrogenase from Aspergillus niger and Aspergillus nidulans

Abstract: ~Glucose-6-phosphate dehydrogenase (G6PD; D-glucose &phosphate:NADP+ oxidoreductase, EC 1.1.1.49) has been purified from AspergiZZus nidulans and AspergiZZus niger by a combination of affinity and anion exchange chromatography. A 500-1000-fold purification was obtained and the final enzyme preparations were shown to be pure but not homogeneous. For both fungi the purified enzyme preparation gave two bands on native and denaturing gels. The catalytically active form is a multimer. The molecular mass of the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…Regulation of these enzymes is probably due to an increased NADP:NADPH ratio. The activity of the first enzyme, glucose 6-phosphate dehydrogenase, is known to be regulated by NADP:NADPH levels [50]. Larochelle et al [51] showed in yeast that transcription of the corresponding gene was also affected by the NADPH level and they attributed this to a transcription factor Stb5.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of these enzymes is probably due to an increased NADP:NADPH ratio. The activity of the first enzyme, glucose 6-phosphate dehydrogenase, is known to be regulated by NADP:NADPH levels [50]. Larochelle et al [51] showed in yeast that transcription of the corresponding gene was also affected by the NADPH level and they attributed this to a transcription factor Stb5.…”
Section: Resultsmentioning
confidence: 99%
“…According to the specificity of coenzyme, G6PDH can be divided into three categories: NADP [27], A. nidulans [27], A. parasiticus [28] and A. aculeatus [29], also exhibited strict specificity towards NADP + . In all NADP + preferred G6PDHs, the conserved Arg residue was revealed and identified as a determinant in the NADP + specificity [21].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the use of cell‐free extracts, not only the activity of glucose‐6‐phosphate dehydrogenase but also the activity of the 6‐phosphogluconate dehydrogenase was measured. The described method was slightly modified [26]. A typical assay in a final volume of 1 mL contained (in m m ) 50 Mops, pH 7.5; 1 glucose‐6‐phosphate, 1 NADP, 5 EDTA and cell‐free extract.…”
mentioning
confidence: 99%